2008
DOI: 10.1158/1078-0432.ccr-07-4181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GRP75 as an Independent Favorable Prognostic Marker of Neuroblastoma by a Proteomics Analysis

Abstract: Purpose: Neuroblastoma (NB) is a heterogeneous neoplasm. Detailed biological discrimination is critical for the effective treatment of this disease. Because the tumor behavior of NB is closely associated with the histologic state of differentiation, we thus aimed to identify novel differentiation-associated markers of NB with prognostic implication. Experimental Design: A human NB cell line SH-SY5Y was used as a model system to explore potential biomarkers for the differentiation of NB by proteomic analyses. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…For evaluation of the effect of cell differentiation on IMP3 expression, NB cells were treated with 10 lM all-trans retinoic acid (RA). (24) Cells were harvested before and after RA treatment for 1, 3, and 5 days. The protein expression levels of IMP3 were evaluated by Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For evaluation of the effect of cell differentiation on IMP3 expression, NB cells were treated with 10 lM all-trans retinoic acid (RA). (24) Cells were harvested before and after RA treatment for 1, 3, and 5 days. The protein expression levels of IMP3 were evaluated by Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that mortalin translocates into the nucleus, where it interacts with the retinoic acid receptor to augment retinoic acid -elicited neuronal differentiation (Shih et al, 2011). Interestingly, mortalin is upregulated in retinoic acid-treated neuroblastoma cells and in patients suffering from neuroblastoma (Hsu et al, 2008). Experimental studies confirmed that mortalin interacts with the cellular protein p53 Mizukoshi et al, 2001;Wadhwa et al, 2003).…”
Section: The Role Of Mortalin In Cancermentioning
confidence: 97%
“…19,27 Therefore, expression of B4GALNT3 in all 87 NB tumor tissues was examined by IHC analysis. Positive B4GALNT3 staining was observed specifically in the cytoplasm of ganglion cells of GNB tumor tissues ( Figure 1A); however, expression was negligible in schwannian stromal cells.…”
Section: B4galnt3 Expression Correlates With the Differentiation Statmentioning
confidence: 99%